Internalizing the Social Care Value of Elementary School Students through Character Education - Prihatina, Sifa Adriani; Sukarno, Sukarno; Triyanto, Triyanto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Character education is important for instilling good morals in students, including social care values. This study aims to discover more deeply how schools internalize social care values through character education in elementary schools. Character education makes students good citizens who care about social problems in their immediate environment. The research design used is descriptive qualitative research with a case study model. Researchers used interviews (structured) and observation with educators and students to collect data. Data was validated based on the character education triangulation rubric in learning. Results of the study show that overall the internalization of social care values through character education at Muhammadiyah 1 Elementary School of Surakarta has been successfully carried out through value transformation, namely various strategies such as; character formation and empathy towards others, habituation of social caring attitude; the teacher gives constructive reprimands; The teacher also acts as a role model by setting an example in socially caring behavior and peer tutoring. This result is also strengthened by changes in student attitudes, such as respecting the school community; help a friend in need. This research implies that all relevant stakeholders must continue to improve and be consistent with changes in student behavior.